2019
DOI: 10.1182/blood-2019-130023
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Bleeding Risk Assessment in a Cohort of Children with Low Levels of Von Willebrand Factor

Abstract: Background: Identifying perioperative bleeding risk in pediatric patients undergoing major surgery is challenging because personal history is often not sufficiently informative and laboratory tests are also more susceptible to pre-analytical variables. Children with low Willebrand add further uncertainty in the treatment options. The aim of this study was to evaluate practices to assess hemorrhagic risk and manage bleeding prophylaxis in children with low von Willebrand factor levels (30 and 50 IU/dL; low VWF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…7,8 Moreover, HMB is among the most common symptoms associated with low VWF, with associated iron deficiency, anemia, transfusion requirement, and hospitalization in some patients, consistent with previously published findings in adults. 7,8 Compared with other pediatric studies, [11][12][13] our study is the first to illustrate the frequency and severity of bleeding manifestations in this young population. The prevalence of clinically significant bleeding and resultant complications in adolescents with low VWF is high and supports the need for prompt intervention with hemostatic and/or hormonal therapy.…”
Section: Outcome and Complications Of Bleedingmentioning
confidence: 83%
See 1 more Smart Citation
“…7,8 Moreover, HMB is among the most common symptoms associated with low VWF, with associated iron deficiency, anemia, transfusion requirement, and hospitalization in some patients, consistent with previously published findings in adults. 7,8 Compared with other pediatric studies, [11][12][13] our study is the first to illustrate the frequency and severity of bleeding manifestations in this young population. The prevalence of clinically significant bleeding and resultant complications in adolescents with low VWF is high and supports the need for prompt intervention with hemostatic and/or hormonal therapy.…”
Section: Outcome and Complications Of Bleedingmentioning
confidence: 83%
“…12 Pollio and colleagues reported increased perioperative bleeding risk in children with low VWF compared with healthy controls. 13 Our study is the first to evaluate the bleeding spectrum and severity in adolescent females with HMB and low VWF utilizing HMB and overall bleeding assessment tools (ie, PBAC and BAT score, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the perioperative setting, Gill et al did not find an association between bleeding and low VWF levels. However, Shui et al advocate for systematic evaluation of these patients with a bleeding assessment tool because Pollio et al reported increased perioperative bleeding risk when compared with healthy controls. The US multicenter study on female adolescents with low VWF and HMB reported that 15% of their cohort experienced significant bleeding with dental extraction and surgery …”
Section: Clinical Bleeding Phenotypementioning
confidence: 99%